Acquiring the Philosophical Habit - Sokolowski, Robert (Theology today, 1987)
“The finest outcome of a theological education would be the formation of a preacher or a teacher who spontaneously thinks in this way: someone who appreciates the nuances, contours, definitions, and shapes of important human things and can articulate them clearly; someone who has philosophical understanding, and who can also place these natural things into the light that revelation can bring to them; someone who can bring out the further truth that revelation adds to what we know by reason.”